(untitled) (Conference on English Language Teaching, 2023)
This study focuses on analyzing the semiotics of infographics used in health communication, particularly in the context of COVID-19 control and prevention issued by the Department of Health (DOH) in the Philippines. The objective is to identify, categorize, and interpret the visual signs employed in these infographics, considering their denotative and connotative meanings. The study follows qualitative and interpretative context analysis methods, using Charles Sanders Peirce’s semiotic theory as the framework. The researchers will carefully examine the visual content, including objects, people, colors, and shapes. Ethical considerations such as credibility, trustworthiness, transferability, confirmability, and dependability will be addressed. The research corpus consists of five infographics issued by the DOH, each targeting different audiences and covering various aspects of COVID-19. The findings reveal a range of visual signs, including representations of respiratory symptoms, hand hygiene practices, medical professionals, news updates, and communication methods. Wearing face masks, seeking medical advice, and following proper etiquette is emphasized. The color schemes and symbols effectively convey urgency, caution, and guidance. Visual signs in the infographics play a crucial role in raising awareness and promoting public health measures during the COVID-19 pandemic which contribute to a comprehensive understanding of the messages conveyed through visual communication strategies.